2021
DOI: 10.1371/journal.pbio.3001247
|View full text |Cite|
|
Sign up to set email alerts
|

Fungal and host protein persulfidation are functionally correlated and modulate both virulence and antifungal response

Abstract: Aspergillus fumigatus is a human fungal pathogen that can cause devastating pulmonary infections, termed “aspergilloses,” in individuals suffering immune imbalances or underlying lung conditions. As rapid adaptation to stress is crucial for the outcome of the host–pathogen interplay, here we investigated the role of the versatile posttranslational modification (PTM) persulfidation for both fungal virulence and antifungal host defense. We show that an A. fumigatus mutant with low persulfidation levels is more s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…A. fumigatus is a fungal pathogen that can cause devastating pulmonary infections in individuals suffering from an immune imbalance or underlying lung conditions. 21 Aspergillus infection can also cause or aggravate the immune imbalance. 22 We believe that, because of mutation of the PRF1 gene in our patient, she had a genetic immune response disorder.…”
Section: Discussionmentioning
confidence: 99%
“…A. fumigatus is a fungal pathogen that can cause devastating pulmonary infections in individuals suffering from an immune imbalance or underlying lung conditions. 21 Aspergillus infection can also cause or aggravate the immune imbalance. 22 We believe that, because of mutation of the PRF1 gene in our patient, she had a genetic immune response disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Prxs are a good example, with the p K a of the active-site cysteine being below 6 (Wood et al, 2003 ). Indeed, in persulfidome analysis, two Prxs from Aspergillus fumigatus (Aspf3 and PrxA) were found to be persulfidated, and the presence of their disulfide form increased in cells lacking H 2 S-producing enzymes (Sueiro-Olivares et al, 2021 ).…”
Section: Cellular Mechanisms Of Persulfide Formation and Removalmentioning
confidence: 99%
“…Although the exact mechanism that activates H 2 S is still under study, three enzymes that function in sulfur metabolic routes have been shown to also be able to generate H 2 S and be related with the formation of persulfide groups: cystathionine β-synthase (CBS), cystathionine γ-lyase (CTH), and 3-mercaptopyruvate sulfurtransferase (MST) [ 28 , 29 ]. We constructed the three single deletion mutants in A. fumigatus and corroborated that two of them, ΔmecA (CBS) and ΔmecB (CTH), had significantly reduced levels of persulfidation [ 30 ]. Importantly, those mutants grew normally on all tested S-sources, suggesting that the metabolic function of the enzymes is not crucial for the stability of the trans-sulfuration pathway.…”
Section: Persulfidation Is Relevant For a Fumigatus ...mentioning
confidence: 99%
“…We were unable to construct a double mutant, which led us to propose that persulfidation may be an essential cellular process that cannot be fully disrupted. Compared with the wild type, the ΔmecB mutant was killed to a higher degree by human and murine host effector cells (including macrophages, neutrophils and epithelial cells) and had significantly reduced virulence in two murine models, leukopenic and corticosteroid, of invasive pulmonary aspergillosis [ 30 ]. Therefore, correct levels of protein persulfidation are important for A. fumigatus pathogenic potential and, consequently, tampering with this process may be a good approach to develop novel antifungal strategies.…”
Section: Persulfidation Is Relevant For a Fumigatus ...mentioning
confidence: 99%